Developing a Juvenile Risk Assessment Instrument for Iowa State Evaluation Capacity Building, 1994-1995 - Huff, David Lynch ([Verlag nicht ermittelbar], 2000)
This study was undertaken to address Iowa's inability to classify juveniles at risk of recidivism uniformly across the state by creating and testing a proposed risk assessment instrument. It was anticipated that the risk assessment instrument would be useful in not only providing the juvenile court officers with a tool to appropriately assess the risk of recidivism, but also in providing "common ground" to treatment staff and other relevant officials to determine whether certain interventions worked better with certain levels of risk than others, and whether limited resources were being appropriately utilized in providing appropriate interventions to juveniles with specific risk scores. To develop the Proposed Iowa Juvenile Court Intake Risk Assessment, a team of juvenile court representatives from all eight judicial districts in Iowa, consisting of juvenile court officers, intake officers, and supervisors, designed a risk assessment test instrument to assess a group of juveniles at intake during a one-month period between October and November 1994. The follow-up data collection was conducted by chief juvenile court officers eight months after the original data collection. The purpose of the follow-up was to gather data regarding reoffending. Risk assessment variables include types and number of current offenses, prior arrests and adjudication, histories of supervision and service, substance use and abuse, runaway occurrences, peer relationships, gang affiliation, attitude during intake interview, level of parental control, schooling status (dropped out, graduated, truant), type of current school, discipline problems, suspensions at school, current employment, history of family problems, and reoffending. Demographic variables include offender's sex and race.